A theoretical study of metal-organic frameworks - Zwane, Reabetswe Robin (Department of Chemistry, 2020)
Among the options for carbon sequestration, the development of CO2 capture materials has gained momentum over the past two decades. The design and construction of chemical and physical absorbents for the capture of CO2 and clean energy storage are a crucial technology for a sustainable low-carbon future. Metal-organic frameworks (MOFs) provide a new vision for the adsorption of molecules on solid surfaces. The interest in MOFs is owed to their ultrahigh porosity, high surface areas and tuneable pore sizes and shapes. The main objective of this thesis was to adopt a rational predictive capacity used in MOF design to control properties such as framework porosity and flexibility on a molecular scale. The in-silico studies were carried out by using ab initio quantum mechanical approaches such as density functional theory and perturbation theory. In addition, semi-classical methods like the Grand Canonical Monte Carlo (GCMC) approach was also used. A structural motif called vicinal fluorination was adopted to study MOF linkers in isolation and in a framework. An extensive conformational study, in various solvents, was carried out to investigate the effect of vicinal fluorination on the isolated MOF linkers and therefore elucidate their conformational stability. The effect of fluorination on adsorption isotherms was also investigated. Moreover, various fluorination patterns were explored. Adsorption isotherms of a non-fluorinated copperbased MOF based on experimental work, and its various fluorinated analogues were predicted using the GCMC method. It was found that vicinal fluorination is not dominant in controlling conformations of some MOF linkers. Rather, an interplay of interactions, including solute and steric interactions, influence the conformational stability on rotational profiles. However, vicinal fluorination was shown to control the flexibility of the linkers used in MOFs as it controls the force constants around the minima of rotational profiles of isolated MOF linkers. The study also highlighted the importance of the solvent on the relative energies of the linker conformations – this has a potential impact on the synthesis of MOFs. With the help of computational methods and validation from experimental data, the structural and sorption properties of the framework, upon fluorination, were shown to have consequences on the adsorption properties of the MOF. Vicinally fluorinated frameworks were shown to have higher uptakes at a low temperature and low pressures.